2021
DOI: 10.1016/j.bbrep.2021.100936
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic response to cadmium by Impatiens glandulifera: A preliminary investigation

Abstract: This paper aims to develop our understanding of the effect of cadmium (Cd) on Impatiens glandulifera , a recently identified potential Cd hyperaccumulator. Impatiens glandulifera plants were exposed to three concentrations of Cd (20, 60 and 90 mg/kg) and were sampled at two timepoints (one and seven days) to investigate the stress response of I. glandulifera to Cd. Cd can induce oxidative stress in plants, triggering overproduction of reactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…As a non-essential element, Cd can produce serious toxic effects on plants physiologically and can detriment plants' morphological, physiological, and molecular characteristics (He et al, 2017;Rasafi et al, 2020). Numerous academic studies found that Cd can inhibit plant growth and development by affecting multiple metabolic pathways such as plant photosynthesis, carbohydrate metabolism, nitrogen metabolism, phytohormone signaling, and ion transporter genes and transcription factors (TFs) (Chen et al, 2020;Coakley et al, 2021;Hussain et al, 2021). In recent years, a large number of genes involved in Cd regulation have been detected using transcriptomics (Peng et al, 2015), which provide an understanding of the molecular mechanisms of Cd uptake, transport, and detoxification.…”
Section: Introductionmentioning
confidence: 99%
“…As a non-essential element, Cd can produce serious toxic effects on plants physiologically and can detriment plants' morphological, physiological, and molecular characteristics (He et al, 2017;Rasafi et al, 2020). Numerous academic studies found that Cd can inhibit plant growth and development by affecting multiple metabolic pathways such as plant photosynthesis, carbohydrate metabolism, nitrogen metabolism, phytohormone signaling, and ion transporter genes and transcription factors (TFs) (Chen et al, 2020;Coakley et al, 2021;Hussain et al, 2021). In recent years, a large number of genes involved in Cd regulation have been detected using transcriptomics (Peng et al, 2015), which provide an understanding of the molecular mechanisms of Cd uptake, transport, and detoxification.…”
Section: Introductionmentioning
confidence: 99%